2018
DOI: 10.3389/fphys.2018.01227
|View full text |Cite
|
Sign up to set email alerts
|

Axial Tubule Junctions Activate Atrial Ca2+ Release Across Species

Abstract: Rationale: Recently, abundant axial tubule (AT) membrane structures were identified deep inside atrial myocytes (AMs). Upon excitation, ATs rapidly activate intracellular Ca2+ release and sarcomeric contraction through extensive AT junctions, a cell-specific atrial mechanism. While AT junctions with the sarcoplasmic reticulum contain unusually large clusters of ryanodine receptor 2 (RyR2) Ca2+ release channels in mouse AMs, it remains unclear if similar protein networks and membrane structures exist across spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 74 publications
12
72
0
Order By: Relevance
“…= 0.033, respectively) would be consistent with values measured experimentally, of * 0.3 for ventricular myocytes and up to * 0.1 for sheep atrial myocytes [30]. Typical branch length in atrial myocytes varies from 1.5-2μm in small mammals (rat, mouse, rabbit) to * 2μm in humans [31]. In our model this again would correspond to a F.A.…”
Section: Discussionsupporting
confidence: 89%
“…= 0.033, respectively) would be consistent with values measured experimentally, of * 0.3 for ventricular myocytes and up to * 0.1 for sheep atrial myocytes [30]. Typical branch length in atrial myocytes varies from 1.5-2μm in small mammals (rat, mouse, rabbit) to * 2μm in humans [31]. In our model this again would correspond to a F.A.…”
Section: Discussionsupporting
confidence: 89%
“…However, a recent study has shown transverse tubules in mammalian atrial myocytes including humans [20]. More interesting, a 50% higher density of axial-tubule junctions than of transverse tubules were identified in intact live human atrial myocytes using superresolution microscopy imaging [21]. In this study, more axial-tubules were observed in comparison to transverse-tubules, this will be quantified in future.…”
Section: Discussionmentioning
confidence: 53%
“…Atrial cells have a different t-tubule system than ventricular cells; they are termed transverse-axial tubules (TATs) and present as heterogenous sarcolemmal membrane invaginations that appear near the z-lines and assist in atrial cell contraction (Kirk et al, 2003;Hund and Mohlerp, 2016;Yue et al, 2017). When an AP is initiated, the atrial cells activate intracellular Ca 2+ release and sarcomeric contraction through the TAT junctions (Brandenburg et al, 2018). The existence of the TATs contributes to nearsynchronous Ca 2+ transients and to synchronous subcellular depolarization and intracellular Ca 2+ release.…”
Section: Electro-ca 2+ -Metabolic-mechanical Feedback In Pacemaker Anmentioning
confidence: 99%
“…The existence of the TATs contributes to nearsynchronous Ca 2+ transients and to synchronous subcellular depolarization and intracellular Ca 2+ release. TATs may lead to region-specific electro-mechanical coupling and heterogeneous atrial contraction (Hund and Mohlerp, 2016;Yue et al, 2017;Brandenburg et al, 2018). There is evidence of dense and welldeveloped TATs in both small and large animals (Kirk et al, 2003;Glukhov et al, 2015;Yue et al, 2017;Brandenburg et al, 2018).…”
Section: Electro-ca 2+ -Metabolic-mechanical Feedback In Pacemaker Anmentioning
confidence: 99%
See 1 more Smart Citation